2010
DOI: 10.1111/j.1744-7917.2010.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellulolytic and hemicellulolytic enzyme activity within the Tipula abdominalis (Diptera: Tipulidae) larval gut and characterization of Crocebacterium ilecola gen. nov., sp. nov., isolated from the Tipula abdominalis larval hindgut

Abstract: In forested stream ecosystems of the north and eastern United States, larvae of the aquatic crane fly Tipula abdominalis are important shredders of leaf litter detritus. T. abdominalis larvae harbor a dense and diverse microbial community in their hindgut that may aide in the degradation of lignocellulose. In this study, the activities of cellulolytic and hemicellulolytic enzymes were demonstrated from hindgut extracts and from bacterial isolates using model sugar substrates. One of the bacterial isolates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In Costelytra zealandica (New Zealand grass grub), various hindgut bacteria participate in lignocellulose degradation [4] and some lignocellulose-degrading bacteria have been isolated from the larvae of the scarab beetle Pachnoda marginata [5]. Moreover, bacteria exhibiting cellulose hydrolysis activity have been isolated from other insects, such as Ips pini (North American pine engraver), Dendroctonus frontalis (Southern pine beetle), Saperda vestita (Linden borer) [6] and Tipula abdominalis (giant crane fly) [7]. Symbiotic gut microbes of the fungus-cultivating termites Macrotermes annandalei , Odontotermes yunnanensis and Macrotermes barneyi possess various lignocellulolytic enzyme genes [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Costelytra zealandica (New Zealand grass grub), various hindgut bacteria participate in lignocellulose degradation [4] and some lignocellulose-degrading bacteria have been isolated from the larvae of the scarab beetle Pachnoda marginata [5]. Moreover, bacteria exhibiting cellulose hydrolysis activity have been isolated from other insects, such as Ips pini (North American pine engraver), Dendroctonus frontalis (Southern pine beetle), Saperda vestita (Linden borer) [6] and Tipula abdominalis (giant crane fly) [7]. Symbiotic gut microbes of the fungus-cultivating termites Macrotermes annandalei , Odontotermes yunnanensis and Macrotermes barneyi possess various lignocellulolytic enzyme genes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cyrtotrachelus buqueti also exhibits high lignocellulolytic enzyme activity [18]. However, to date, no studies have investigated the role of snout beetle gut microbiota in lignocellulose degradation, as has been done for termites [8] and other species of beetles [47]. The present study investigates the role of adult and larval C .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they require several enzymes to digest their diet. It has been reported that in many xylophagous-and detritophages-insects, enzymes from symbiotic bacteria such as cellulases, xylanases, and amylases assist in the degradation of the plant-derived materials to release fermentable simple carbohydrates (Warnecke et al, 2007;Rogers and Doran-peterson, 2010;Fabryová et al, 2018).…”
Section: Dietzia Natronolimnaea Acinetobacter Johnsonii Staphylococmentioning
confidence: 99%
“…Huang et al (2010) reviewed the physiochemical properties of the scarab beetle gut at larval stage, the diversity and digestive roles that symbiotic microflora play in the scarab gut, and they further discussed the potential for applying these digestive processes in artificial bioreactors. Exploring another specific cellulose-consuming insect from the order Diptera (crane fly), which is a leaf shredding aquatic insect that lives in forested ecosystems, Rogers and Doran-Peterson (2010) have reported the analysis of cellulolytic and hemicellulolytic enzyme activity within this insect gut (larval stage). They also identified and characterized novel cellulolytic bacterial species isolated from its gut system.…”
Section: Role Of Cellulasesmentioning
confidence: 99%